IR780 Based Sonotherapeutic Nanoparticles to Combat Multidrug-Resistant Bacterial Infections - Huang, Biying; Wang, Long; Tang, Kui; Chen, Sijie; Xu, Yan; Liao, Haiqin; Niu, Chengcheng (Frontiers in Chemistry, 2022)
Multidrug-resistant (MDR) bacterial strains have emerged and weakened the therapeutic effects of antibacterial drugs. Sonodynamic therapy (SDT) takes advantage of noninvasiveness and deep tissue-penetrating features and has been rejuvenated to combat MDR bacteria and their biofilm-associated infections. To improve the efficacy of antibacterial SDT, we first developed IR780-based PLGA nanoparticles as sonosensitizers for high-frequency ultrasound (US)-monitored antibacterial SDT of MRSA myositis by therapeutic low-frequency US. In this study, the developed shell-core-structured IR780@PLGA nanoparticles were designed with a polymer shell PLGA with the sonosensitizer IR780 loaded on. High-frequency diagnostic US was introduced to monitor the sonotherapeutic progression of bacterial myositis by therapeutic low-frequency US. Importantly, the in vitro and in vivo results confirmed that IR780@PLGA nanoparticles combined with US irradiation possess high efficiency for antibacterial therapy. This approach provides a simple and efficient strategy to monitor and combat MDR bacterial infection.